An Analisis Semiotika Peirce pada Logo Gerakan Salam Empat Jari - Gugun Gunawan; Pradianti, Keni (Jurnal Komunitas Bahasa, 2025)
This study aims to examine the meaning contained in the “Four Fingers” logo using Charles Sanders Peirce’s semiotic approach. It employs a qualitative descriptive method, with Peirce’s semiotic theory serving as the analytical framework. Data collection was conducted using a note-taking technique. This research was carried out due to the absence of prior studies addressing this phenomenon from a semiotic perspective. The findings indicate that the message conveyed through the design of the “Four Fingers” logo and its visual campaign is communicatively received by the public. Based on Peirce’s elements of representamen, object, and interpretant, the logo is interpreted as a symbolic call for the public to collectively monitor and prevent potential electoral fraud in the 2024 election, which is perceived as a threat to the principles of democracy in Indonesia. Overall, the results of this study contribute to the richness of semiotic discourse and may serve as a reference for future research.